1999
DOI: 10.1038/sj.bmt.1701897
|View full text |Cite|
|
Sign up to set email alerts
|

Pneumocystis cystoides intestinalis with pneumoperitoneum and pneumoretroperitoneum in a patient with extensive chronic graft-versus-host disease

Abstract: Summary:Pneumatosis cystoides intestinalis is a rare finding of intramural gasfilled cysts in the bowel wall and sometimes free air in the abdomen. A few conditions are reported to cause this disease, one of them being immunosuppression. We describe a 50-year-old Caucasian male with extensive chronic graft-versus-host disease (GVHD) of the gut and skin who developed PCI with pneumoperitoneum and pneumoretroperitoneum. To our knowledge, this is the first report of PCI occurring in a patient with active chronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 7 publications
1
18
1
Order By: Relevance
“…In accordance with results obtained in previous studies [15, 16, 17], the clinical courses of our patients indicate that in the absence of secondary complications a conservative approach should be the treatment of choice for PI following antineoplastic chemotherapy. Since our patients suffered from severe immunosuppression, we chose treatment with empiric broad-spectrum antibiotics including metronidazole additionally to parenteral nutrition in all cases.…”
Section: Discussionsupporting
confidence: 78%
“…In accordance with results obtained in previous studies [15, 16, 17], the clinical courses of our patients indicate that in the absence of secondary complications a conservative approach should be the treatment of choice for PI following antineoplastic chemotherapy. Since our patients suffered from severe immunosuppression, we chose treatment with empiric broad-spectrum antibiotics including metronidazole additionally to parenteral nutrition in all cases.…”
Section: Discussionsupporting
confidence: 78%
“…30 Conservative management includes broad spectrum antibiotics, administration of oxygen at high concentrations, bowel rest, TPN followed by diet of low-flatulence producing carbohydrates when oral feeding is tolerated. 11,31 Galm et al reported five cases of PI following cytotoxic chemotherapy. Patients did not demonstrate signs of peritonitis and they were treated conservatively with metronidazole, piperacillin, tobramycin and TPN.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis is established by endoscopy or radiography and is manifested by multiple thin-walled cysts that develop in the colonic submucosa or subserosa. 1 The secondary form accounts for the majority of cases and is associated with: celiac disease, 2 connective tissue disorders, 3 including systemic lupus erythematosus, 4 infectious enteritis, 5 chronic obstructive pulmonary disease, 6 primary immunodeficiency, 7 acquired immunodeficiency syndrome, 8 leukemia, 9 organ transplantation, 10 bone marrow transplantation 11 and in patients receiving glucocorticoids 12 and chemotherapy. 13 PI traditionally has been managed surgically with a high mortality rate (33-44%).…”
Section: Introductionmentioning
confidence: 99%
“…Thereafter, PI worsened after FEAM conditioning for the auto-HSCT. The decision to proceed to the second transplant with an unrelated donor was of particular concern due to the risk of a further worsening of the PI, especially in the possible case of an intestinal GVHD or of infectious complications [5][6][7]12,13]. However, considering the poor prognostic likelihood of our patient affected by DLBCL resistant to several lines of therapy, we decided to proceed with an allo-HSCT, sharing the decision with the patient and her relatives.…”
Section: Discussionmentioning
confidence: 99%
“…It has been associated with congenital disorders, collagen vascular diseases, acquired immunodeficiency, infection, endoscopic procedures, steroid use and chemotherapy [4][5][6][7][8]. PI is also found in association with organ transplantation and HSCT due to pre-transplant chemotherapy, infections and GVHD after HSCT [9][10][11][12][13]. It is hypothesized that when a pathogenic noxa causes a GI wall disruption necrosis, an increased wall permeability can occur, leading to gas infiltration.…”
Section: Introductionmentioning
confidence: 99%